Término para aclarar o completar la contestación y reconvención, principio de igualdad y el debido proceso - Chiliquinga Álvarez, Emilia Fernanda (2025)
A current issue affecting the justice system is outlined in Article 156 of the General Organic Code of Procedures, which sets a three-day limit for clarifying or completing the response and counterclaim of the defendants. Additionally, it is noted that the plaintiff has five days to clarify or complete the complaint, indicating that the defendants have a shorter term. It is evident that there is inequality generated when defendants do not have the same terms and a reasonable opportunity to present their case under conditions that do not disadvantage them compared to their opponent. It is evident that there is inequality generated when defendants do not have the same terms and a reasonable opportunity to present their case under conditions that do not disadvantage them compared to their opponent. In these cases, the defendants are left defenseless because they do not have adequate mechanisms to access the justice system to protect their rights. The problem is how the term granted by law to clarify or complete the response and counterclaim of the defendants violates the principles of equality and due process. The methodology used a qualitative approach, described through the application of inductive-deductive, analytical-synthetic, and historicallogical methods. The technique used was interviews conducted with a group of legal professionals. Finally, in the discussion, it was demonstrated how the principle of equality and due process for the defendants was violated by having a shorter period to clarify or complete the demand.